Theme and Imagery in Tchicaya U Tam'si's A Triche Coeur - Emil A. Magel (Studies in 20th & 21st Century Literature, 1980)
Partaking of the universal search for self-knowledge, Gerald Felix Tchicaya U Tam'si's A Triche Coeur explores and evaluates the assumptions which shape his African identity. The thematic movement of the volume progresses from his initial state of naive ignorance of the realities of African history to a more mature awareness of it. Through images of uprooting and regeneration, the poet discovers both the blood-stained truth of European colonization of Africa and the traitorous collaboration of its renegades. Casting off the myths of the civilizing mission, the noble savage and the romantic posturings of the Negritude poets, U Tam'si releases himself from their psychological hold on him. Utilizing metaphors and similes which emphasize the discovery process, the poet generates a new vision of himself and urges other 'lost' Africans to follow his footsteps.
Keywords: self-knowledge; Gerald Felix Tchicaya U Tam& #x27; si; A Triche Coeur; African identity; African history; European colonization of Africa; colonialism; civilizing mission; noble savage; discovery process; identity